Our poisoned waters - Dolan, Edward F. 1924- (New York Cobblehill Books, 1997)
Examines the serious problem of water pollution in both fresh and salt water bodies throughout the world and describes what is being done about it.
Includes bibliographical references (p. [111]-116) and index.
Keywords: Water -- Pollution -- Juvenile literature; Water -- Pollution; Pollution